2006
DOI: 10.3200/jrlp.140.1.53-67
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Factorial Invariance in Need for Cognition Using Hispanic and Anglo Samples

Abstract: The Need for Cognition Scale

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
3
1
1
Order By: Relevance
“…Regarding scale invariance, although other studies have confirmed its invariance with respect to age or for samples of different ethnicities (Culhane et al, 2006; Soubelet & Salthouse, 2017), in this study the NFC Scale (18 items) was variant both in relation to gender and type of sample (managers and nonmanagers). This makes the Scale less generalizable, suggesting a susceptibility to population type.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Regarding scale invariance, although other studies have confirmed its invariance with respect to age or for samples of different ethnicities (Culhane et al, 2006; Soubelet & Salthouse, 2017), in this study the NFC Scale (18 items) was variant both in relation to gender and type of sample (managers and nonmanagers). This makes the Scale less generalizable, suggesting a susceptibility to population type.…”
Section: Discussioncontrasting
confidence: 60%
“…Some studies, as well, have sought to assess the ethnic invariance (Anglo, African American, Hispanic, and other ethnicities) of the Scale (Culhane, Morera, & Wtason, 2006). They also have looked at different age-groups (range between 18 and 99 years; e.g., Soubelet & Salthouse, 2017), noting its metric invariance in this application.…”
Section: Nfc and Management Activitymentioning
confidence: 99%
“…Participants indicated how much they agree with each statement on a 5-point scale, ranging from extremely unlike me (1) to extremely like me (5). The measure has been shown to be reliable, valid and appropriate for use in diverse populations (Culhane, Morera, & Hosch, 2004;Culhane, Morera, & Watson, 2006).…”
Section: Methodsmentioning
confidence: 98%
“…An example of this approach is found in Culhane, Morera, and Watson (2006), who tested the Need for Cognition Scale-Short Form (NCS-SF) among 608 Hispanic- and Anglo-American college students. The authors sequentially tested confirmatory factor analytic models for weak, strong, and strict factorial invariance.…”
Section: Measurement Equivalence and Diagnostic Validitymentioning
confidence: 99%